PROSES BERPIKIR SISWA KELAS VIII SMP NEGERI 25 SURAKARTA DALAM MEMECAHKAN MASALAH MATEMATIKA DITINJAU DARI TIPE KEPRIBADIAN EXTROVERT-INTROVERT PADA MATERI PERSAMAAN GARIS LURUS - Permatasari, Nisa; Budiyono, Budiyono; Slamet, Isnandar (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The objective of this research was to describethe 8th grade studentsâs thinking process of SMP Negeri 25 Surakarta. The subjects were students of 8th E who has an extrovert and introvert personality. The thinking process was the thought process of assimilation and accommodation in solving mathematical problems based on the type of Krulik and Rudnick on a straight-line equation. The technique of data collection that used was snowball-sampling which the subject stopped when data saturation. Obtained three extrovert students and three introvert students. The validation of data was carried out with time triangulation. The result of research showed that the thinking process of extrovert students in solving mathematical problems based on the type of Krulik and Rudnick step was as follows 1) In read and think step, the used of thinking process was assimilation; 2) In explore and plan step, the used of thinking process was imperfect assimilation; 3) In select a strategy step, the used of thinking process was imperfect assimilation; 4) In find an answer step, the used of thinking process was imperfect assimilation; 5) In reflect and extend step, the used of thinking process was accommodation. The thinking process of introvert students in solving mathematical problems based on the type of Krulik and Rudnick step was as follows: 1) In read and think step, the used of thinking process was assimilation; 2) In explore and plan step, the used of thinking process was assimilation; 3) In select a strategy step, the used of thinking process was imperfect assimilation; 4) In find an answer step, the used of thinking process was assimilation; 5) In reflect and extend step, the used of thinking process was a imperfect assimilation.Keywords: Assimilation and Accommodation, Extrovert and Introvert, Problem Solving.Â